Analyze The Potential Of Sabang Free Port As A Transshipment Hub Of The Belt Road Initiative - Reza Fahlevi; Chairul Iqbal Aziz (Publikasi Indonesia, 2025)
This study aims to analyze the potential of Sabang Free Port as a transshipment hub within the Belt and Road Initiative (BRI) and to identify the challenges and opportunities for its development. The research employs a qualitative approach with a descriptive-analytical method. Data is collected through literature review, policy document analysis, and interviews with stakeholders, including academics and maritime industry practitioners. The findings indicate that Sabang Port has a strategic geographical advantage along the Malacca Strait and deep waters that support large vessels. However, infrastructure limitations, low trade activity, and minimal investment pose significant obstacles to its development. The discussion highlights the need for infrastructure improvements, investment promotion, and policy reinforcement to attract more maritime industry players. The study concludes that while Sabang has the potential to become an international transshipment hub, a comprehensive strategy from both the government and private sector is required to enhance its competitiveness. The successful implementation of appropriate policies will determine Sabang’s role in supporting global maritime connectivity through the BRI.